Intuitions in Human-Technology Interaction Design - Saariluoma, Pertti (Human Technology, 2011)
While science is interested in how things are, design concerns more how things should be in the world. While both focus on the common the pursuit of improving the quality of human life, they are different in many respects. One of the differences is the way intuition is applied.